Inter-temporal Cost Allocation and Managerial Investment Incentives - William P. Rogerson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
This paper provides a formal analysis of how managerial investment incentives are affected by alternative allocation rules when managerial compensation is based on accounting measure of income which include allocations for investment expenditures. The major result is that a unique allocation rule exists, called the relative marginal benefits (RAB) rule, which always induces the manager to choose the efficient investment, no matter how the manager values his own personal cash flows from wage compensation over time and no matter what wage schedule is in place (so long as wages are weakly increeasing each period's income). That is, the same allocation rule works for every possible managerial utility function over wage payments and every monotone wage function over accounting incomes. Thus the firm can choose an allocation rule which induces efficient investment choices without knowing the manager's preferences. Furthermore, since the same rule works for every monotone wage schedule, the firm is left a "degree of freedom" to choose the wage schedule to solve some other incentive problem. In addition to demonstrating the optimality of the RMB rule and describing its properties, the paper considers how currently used allocation rules qualitatively affect managers' investment incentives. It is shown that the practice of expensing intangible assets (i.e., allocating 100 percent of the cost to the current perios) causes mangers to underinvest relative to the efficient level. The case of tangible assets is more complicated. It appears that current practices may cause either underinvestment or overinvestment, depending on various factor described in more detail in the text.
Keywords: 330